Características sociodemográficas y satisfacción de usuarios en consultorios externos Hospital Regional de Loreto Iquitos 2023 - Alfaro Souza, Jhuliana Estefani (2024)
The objective was to determine the relationship between sociodemographic characteristics and satisfaction of users of outpatient clinics at the Regional Hospital of Loreto, Iquitos 2023. A quantitative approach was used with a non experimental, descriptive, correlational and cross-sectional design. The sample was made up of 125 users of outpatient clinics at the Loreto Regional Hospital. The technique was the survey and the instruments were the Questionnaire of sociodemographic characteristics of external users of outpatient consultation and the Satisfaction with Health Services Scale-S5/22. SPSS statistical software version 24.0 was used for data analysis and the chi square statistical test (χ2) was used for correlation analysis. According to the results, 60.8% were between 30 and 59 years old, 63.2% were female, 42.4% had secondary education, 65.6% were patients and 75.2% had SIS. Regarding the level of satisfaction, 85.6% were moderately satisfied, 8.8% were satisfied and the remaining 5.6% were dissatisfied. In conclusion, an association was found with: Type of user (p=0,013) and Type of insurance (p=0,008). Likewise, no association was found with: Age (p=0.078), Sex (p=0.072) and Level of education (p=0.274)